PERSEPSI KEGUNAAN, KEMUDAHAN PENGGUNAAN, KEAMANAN DAN PRIVASI SERTA KEPERCAYAAN DALAM PENGGUNAAN ZAKAT ONLINE: DENGAN PENDEKATAN TAM - Bahana Wiharjo; Achsania Hendratmi (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This research aim to examine the effect of perception usefulness, ease of use,  security and privacy and trust on online zakat in Indonesian. The sample of this study is the Muslim community in Indonesian who have fulfilled the provisions to pay zakat as many as 31 respondents. The data use are primary data collected using a questionnaire through google form. Indicators of research variables are measured using differential semantic scales 1 to 7. This study proves that usefulness, security and privacy as well as thrust have a significant positive on the use zakat online. Effect on the ease of use the result has a significant negative effect on the use of zakat online. The study also found that the criteria of individuals (respondent) who were relatively young and male were not problematic with the complexity of the online zakat website.Keywords: ease of use, usefulness, security and privacy, trust, online zakat usage, zakatREFERENCES Adam, B. (1992). Modern times: The technology connection and its implications for social theory. Time & SocAgarwal, R., & Prasad, J. (1999). Are individual differences germane to the acceptance of new information technologies? Decision sciences, 30(2), 361-391. Agranoff, M. H. (1991). Controlling the threat to personal privacy corporate policies must be created. Information System Management, 8(3), 18-52. Ahmad, N. N., Tarmidi, M., Ridzwan, I. U., Hamid, M. A., & Roni, R. A. (2014). The Application of Unified Theory of Acceptance and Use of Technology (UTAUT) for Predicting the Usage of E-Zakat Online System. International Journal of Science and Research (IJSR), 3(4), 63-67. Alam, S. S., Musa, R., & Hassan, F. (2009). Corporate customers’ adoption of0internet banking: Case of Klang Valley business firm in Malaysia. International Journal of Business and Management, 4(4), 13. Amin, H., Abdul‐Rahman, A. R., Ramayah, T., Supinah, R., &Mohd‐Aris, M. (2014).Determinants of online waqf acceptance: An empirical investigation. The Electronic Journal of Information Systems in Developing Countries, 60(1), 1- 18.Chin, W. W., & Todd, P. A. (1995). On the use, usefulness, and ease of use of structural equation modeling in MIS research: a note of caution. MIS quarterly, 237-246. Chung, N., dan S. J. Kwon. (2009). Effect of trust level on mobile banking  satisfaction: a multi-group analysis of information system success instruments. Behaviour & Information Technology, 28(6), 549-562.Czara, S. I; Hammond, K.; Blascovich, J. J.; and Swede, H (1989). Age related differences in Learning to use text editing system. Behavior and information technology, 8,4 , 309-319 .Davis, F. D. (1989). Perceived usefulness, perceived ease of use, and user acceptance  of information technology. MIS quarterly, 319-340. Flavián, C., Guinalíu, M., & Torres, E. (2005). The influence of corporate image on consumer trust: A comparative analysis in traditional versus internet banking. Internet Research, 15(4), 447-470. Harrison, A. W., dan R. K. Rainer Jr. (1992). The influence of individual differences on skill in end-user computing. Journal of Management Information Systems, 9(1), 93-111.Ibrahim, M. F. (2014). Sistempengurusan zakat di Malaysia: Analisis strategipenyebaran maklumat menerusil aman sesawang. Jurnal Pengurusan(UKM Journal of Management), 42. Jamaludin, N., Wahab, N. A., & Hamed, A. B. (2017). Muslim Perception on Online Zakat Usage in Kuala Lumpur. Kalakota, R., &Whinston, A. B. (1997). Electronic commerce: a manager's guide: Addison-Wesley Professional.Kaslam, S. (2009). Governing zakat as a social institution: The Malaysian perspective. Social and Management Research Journal, 6(1), 15-32. Kleijnen, M., Wetzels, M., & De Ruyter, K. (2004). Consumer acceptance of wirelessfinance. Journal of financial services marketing, 8(3), 206-217. Kusuma, H., &Susilowati, D. (2007). Determinan Pengadopsian Layanan Internet Banking: Perspektif Konsumen Perbankan Daerah Istimewa Yogyakarta. JurnalAkuntansi dan Auditing Indonesia, 11(2). Luarn, P., & Lin, H.-H. (2005). Toward an understanding of the behavioral intention to use mobile banking. Computers in human behavior, 21(6), 873-891. Morgan, R. M., & Hunt, S. D. (1994). The commitment-trust theory of relationship  marketing. The journal of marketing, 20-38. Nickell, G.S., and Pinto, J.N.(1989) The computer attitude scale. Computers in Human Behav- ior, 2, 301-306Poon, W.-C. (2007). Users' adoption of e-banking services: the Malaysian perspective. Journal of Business & Industrial Marketing, 23(1), 59-69. Rais, I. (2009). Muzakki dan Kriterianya Dalam Tinjauan Fikih Zakat. Al-Iqtishad: Jurnal IlmuEkonomi Syariah, 1(1). Raub, A. C. (1981). Correlates of computer anxiety in college students.Rexha, N., Kingshott, R. P. J., & Shang Shang Aw, A. (2003). The impact of the relational plan on adoption of electronic banking. Journal of services marketing, 17(1), 53-67. Rosland, A. B., Romli, N. B., &Borhan, J. T. (2012). Contract (akad) in online  banking. International Journal of Computer Applications, 60(18). Sadeq, A. M. (1997). Poverty alleviation: an Islamic perspective. Humanomics, 13(3), 110-134. Sathye, M. (1999). Adoption of Internet banking by Australian consumers: an empirical investigation. International Journal of bank marketing, 17(7), 324-334. Suh, B., & Han, I. (2002). Effect of trust on customer acceptance of Internet banking.  Electronic Commerce research and applications, 1(3-4), 247-263. Tan, G. W.-H., Chong, C.-K., Ooi, K.-B., & Chong, A. Y.-L. (2010). The adoption of online banking in Malaysia: an empirical analysis. International Journal of Business and Management Science, 3(2), 169. Triyuwono, I. (2004). Trust (Amanah), the divine symbol: Interpretations in the context of Islamic banking and accounting practices. Paper presented at the Fourth Asia Pacific Interdisciplinary Research in Accounting Conference.Wahab, N. A., & Abdul-Rahman, A. (2015). Efficiency of zakat institutions and its  determinants. Access to Financ and Human Development—Essays on Zakah, Awqaf and Microfinance, 33. Wahab, N. A., & Rahim Abdul Rahman, A. (2011). A framework to analyse the efficiency and governance of zakat institutions. Journal of Islamic Accounting and Business Research, 2(1), 43-62. Wardiana, W. (2002). Perkembangan teknologi informasi di Indonesia. Yaakub, N. A., Ramli, N. M., Muhamed, N. A., & Muhammad, I. (2016). Analysis of  e-payment applications: a case study of one of the zakat institutions in malaysia. Journal of Techno Social, 8(2). Yousafzai, S. Y., Pallister, J. G., &Foxall, G. R. (2003). A proposed model of e-trust for electronic banking. Technovation, 23(11), 847-860.